PERANCANGAN SISTEM INFORMASI PENDAFTARAN ONLINE BERBASIS WEB PADA PAUD ASSIBYAN SERANG BANTEN - Zulham Efendi (2022)
ABSTRACT In the era of digital development and the ongoing Covid-19 pandemic, schools are temporarily closed, but every year the school carries out the process of accepting new students, in the process of accepting new students carried out by PAUD Assibyan Serang Banten still using the manual method by way of parents of prospective students. just come directly to school to fill out paper forms with conditions like this, the school needs an appropriate marketing strategy for new student admissions, schools must still be able to carry out the new student admissions process so that many candidates register without having to come to school directly and other people prospective new students really need information about school registration quickly and precisely, therefore the right solution is to create a website-based online registration system that is connected to the internet so that it can make it easier for parents of prospective new students to register advice anywhere and anytime so that parents of prospective participants can carry out the registration process without having to come to school. The development of this online registration information system is designed using the waterfall method with stages, namely needs analysis, design, program code creation, testing and maintenance. Keywords: PHP, Registration, Early Childhood Education, Website, Student